Analysis of the Free Nutritious Meal Program from the Perspective of Maqasid Al-Shariah - Abu Bakar; Habibullah Habibullah; Muhammad Idris (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
The Free Nutritious Meals Program is a social intervention policy aimed at improving public access to nutritious food as an effort to strengthen human resource quality, particularly among vulnerable groups such as school-age children. This study aims to analyze the implementation of the Free Nutritious Meals Program from the perspective of Maqashid al-Sharia, which encompasses the five essential objectives of Islamic law (al-dharuriyyat), namely hifz al-din (protection of religion), hifz al-nafs (protection of life), hifz al-‘aql (protection of intellect), hifz al-nasl (protection of progeny), and hifz al-mal (protection of wealth). The study employs a qualitative approach through a literature review and conceptual analysis of public policy and the principles of Maqashid al-Sharia. Data were obtained from policy documents, program reports, and academic studies related to nutrition, food policy, and social welfare. The analysis examines the alignment of the program's objectives, implementation mechanisms, and potential impacts with the fulfillment of society's basic needs within the framework of Islamic law. The findings indicate that the Free Nutritious Meals Program is strongly relevant to hifz al-nafs through nutritional fulfillment and stunting prevention, while also supporting hifz al-‘aql by improving students' concentration and learning capacity. The program also contributes to hifz al-nasl through investment in the health of future generations and to hifz al-mal by reducing household economic burdens. However, governance, distribution, transparency, and sustainability still need to be strengthened to ensure that program implementation is increasingly aligned with the principles of justice (al-‘adl) and public benefit (maslahah ‘ammah).